ZmMYB14 is an important transcription factor involved in the regulation of the activity of the ZmBT1 promoter in starch biosynthesis in maize. (10th August 2017) - Xiao, Qianlin; Wang, Yayun; Du, Jia; Li, Hui; Wei, Bin; Wang, Yongbin; Li, Yangping; Yu, Guowu; Liu, Hanmei; Zhang, Junjie; Liu, Yinghong; Hu, Yufeng; et al.
Abstract : The biosynthesis of starch is a complex process that depends on the regulatory mechanisms of different functional enzymes, and transcriptional regulation plays an important role in this process. Brittle 1, encoded by BT1, is a transporter of adenosine diphosphate‐glucose, which plays an important role in the biosynthesis of starch in the endosperm of cereals. Here, we report that the promoter ( pZmBT1 ) of the maize BT1 homolog, ZmBT1, contains an MBSI site (TAACTG), which is important for its activity. Moreover, high expression level of the gene for ZmMYB14 transcription factor was observed in the maize endosperm; its expression pattern was similar to those of the starch synthesis‐related genes in maize seeds. ZmMYB14 is a typical 2R‐MYB transcription factor localized in the nucleus and possessed transcriptional activation activity. ZmMYB14 could bind to the region of pZmBT1 from −280 to −151 bp and promote its activity through the TAACTG site. It was also observed to promote the activity of pZmSh2, pZmBt2, pZmGBSSI, pZmSSI, and pZmSBE1 in the maize endosperm in transient gene overexpression assays. Furthermore, ZmMYB14 was also shown to bind directly to the promoters of six starch‐synthesizing genes, ZmGBSSI, ZmSSI, ZmSSIIa, ZmSBE1, ZmISA1, and ZmISA2 in yeast. These findings indicate that ZmMYB14 functions as a key regulator of ZmBT1 and is closely related to the biosynthesis of starch. Our results provide crucial information related to the regulation of starch biosynthesis in maize and would be helpful in devising strategies for modulating starch production in maize endosperm. Abstract : ZmMYB14, functions as a key regulator of starch biosynthesis, could bind to the region of pZmBT1 from −280 bp to −151 bp and mediates its activity through the TAACTG site. It is also observed to bind directly to the promoters of six starch‐synthesizing genes, and promote the activity of pZmSh2, pZmBt2, pZmGBSSI, pZmSSI, and pZmSBE1 in the maize endosperm in transient gene overexpression assays.